2009
DOI: 10.1186/1471-2121-10-77
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol exerts dual effects on calcium homeostasis in CCK-8-stimulated mouse pancreatic acinar cells

Abstract: Background: A significant percentage of patients with pancreatitis often presents a history of excessive alcohol consumption. Nevertheless, the patho-physiological effect of ethanol on pancreatitis remains poorly understood. In the present study, we have investigated the early effects of acute ethanol exposure on CCK-8-evoked Ca 2+ signals in mouse pancreatic acinar cells. Changes in [Ca 2+ ] i and ROS production were analyzed employing fluorescence techniques after loading cells with fura-2 or CM-H 2 DCFDA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…By itself, a concentration of 850 mM was required to evoke a small Ca 2ϩ transient (6). There is also evidence that ethanol either directly or through generation of reactive oxygen species causes Ca 2ϩ influx (35,36). However, several reports implicate a role for ethanol metabolites as the actual mediators of aberrant Ca 2ϩ signaling in acinar cells (34,37).…”
Section: Discussionmentioning
confidence: 99%
“…By itself, a concentration of 850 mM was required to evoke a small Ca 2ϩ transient (6). There is also evidence that ethanol either directly or through generation of reactive oxygen species causes Ca 2ϩ influx (35,36). However, several reports implicate a role for ethanol metabolites as the actual mediators of aberrant Ca 2ϩ signaling in acinar cells (34,37).…”
Section: Discussionmentioning
confidence: 99%
“…These patterns of changes in [Ca 2? ] c have been previously observed in both tumor and non-tumor pancreatic cells (Del Castillo-Vaquero et al 2010;Fernandez-Sanchez et al 2009;Gonzalez et al 1997).…”
Section: Analysis Of Intracellular Free-camentioning
confidence: 70%
“…Specifically, it has been shown that after treatment of isolated pancreatic acinar cells either with EtOH or its non-oxidative metabolites, physiological concentrations of secretagogue induces sustained increases in [Ca 2ϩ ] cyto that are no longer limited to the apical pole but spread throughout the acinar cell (28,29). Associated with the prolonged aberrant Ca 2ϩ signal is an inhibition of apical zymogen secretion (30), impaired mitochondrial function (i.e.…”
mentioning
confidence: 99%